Filipino Gurus’ Perspectives on Philippine Teacher Protection Act and Their Reflections on Student Discipline and Its Present-Day Implementation - Aljon Delmo Galang (JURNAL INOVATIF ILMU PENDIDIKAN, 2020)
When Child Protection Policy (CPP) has been implemented, many teachers strive to maintain discipline and execute the curriculum through instruction. In the worst circumstances, lawsuits related to student discipline and classroom management have been filed against teachers. With this, the Philippine Congress created the bill Teacher Protection Act (TPA) primarily authored by Antonio L. Tinio, France L. Castro, and Ramon H. Durano VI. This act protects the teachers from students of bad behavior, abusing the legal empowerment from CPP. This shift leads to the conduct of this study. This phenomenological study aims to give insights about the bill (the phenomenon) and to gauge how the teacher participants perceive it (the perception). An interview is conducted among five (5) tenured teacher participants. They are asked to assess the house bill content and its future implications to provide insights to the teachers, other stakeholders, and the lawmakers. The investigation identifies that: (a) CPP is a hindrance to student discipline; (b) TPA must be immediately implemented; (c) the act is perceived to be a protection, but must be improved; (d) there are no clear guidelines to implement the act so far; (e) legal assistance in cases related to student discipline and classroom management is one of the best features of the act; (f) equality between students and teachers are perceived to be significant; (g) financial constraint is a consideration to be made to successfully implement the act; and (h) though the participants may single out some points to re-consider, they are still positive towards the act and what it can do for the welfare of the teachers.Keywords: Teacher Protection Act, Child Protection Policy, Student Discipline, Classroom Management. DOI: http://dx.doi.org/10.23960/jiip.v2i2.21786